Flammulina velutipes mycorrhizae dietary fiber improves lipid metabolism disorders in obese mice through activating AMPK signaling pathway mediated by gut microbiota. (October 2021) - Wang, Wenliang; Yang, Shifa; Song, Shasha; Zhang, Jian; Jia, Fengjuan
Abstract: Mounting evidence shows that dietary fiber (DF) alleviates lipid metabolism disorders in humans and animals by regulating the gut microbiota. However, its action mechanisms remain to be elucidated. Flammulina velutipes ( F. velutipes ) as an edible mushroom is widely cultivated in China and has medicinal values. As a by-product of F. velutipes, the mycorrhizae are rich in high-quality DF and therefore can be used to prepare F. velutipes DF (Fv-DF). The objective of this research aimed to explore whether and how Fv-DF attenuates lipid metabolism disorders in obese mice through the gut microbiota. Here, an obese mice model induced by high-fat diet was established to analyze the effect of Fv-DF supplementation on the lipid metabolism disorders and gut microbiota. The results showed that Fv-DF administration significantly reduced the weight gain, triglycerides and total cholesterol, low-density lipoprotein cholesterol and markedly increased the activity of enzymes related to scavenging ability of oxygen free radicals. The gut microbiota sequencing exhibited that the Fv-DF supplementation increased the level of gut beneficial bacteria, such as Prevotellaceae UCG-001 and Alloprevotella . Western blot analysis revealed the phosphorylated adenosine 5′-monophosphate (AMP)-activated protein kinase ( p -AMPKα) was up-regulated, indicating that AMPK signaling pathway was activated. The activated pathway down-regulated the fatty acid synthase level to decrease lipid synthesis and up-regulated the carnitine palmitoyl transferase-1 level to increase lipid degradation. Altogether, Fv-DF supplementation alleviates lipid metabolism disorders in obese mice by regulating the gut microbiota-mediated AMPK signaling pathway. Graphical abstract: Image 1 Highlights: (1) Fv-DF reduced the weight gain and improved physiological indexes in obese mice. (2) Fv-DF improved the abundance and composition of gut microbiota. (3) The changed microbiota activated AMPK signaling pathway. (4) AMPK pathway activation may be a major contributor to alleviate obesity.